Propuesta de un sistema logístico para la empresa Farma buenos aires s.a.c en la provincia de sullana - Lozano Ayala, David Gonzalo (2017)
The present study was carried out in the premises of the company Farma Buenos Aires SAC, dedicated to the commercialization of medicines, sanitary articles and others of the same kind, where the research is mainly focused on improving the logistic activities found in the company under study. As an essential first step in this study was to diagnose and describe the evidences that turn out to be the effect of poor management in the logistics of the company, bringing with it a meager measurement and control of the excessive and prolonged costs in the respective activities. In order to deal with the negative effects, various tools were used throughout the logistics chain such as the cataloging and classification "ABC" of articles, the system of inventories of periodic revision, methods of selection and evaluation of suppliers. In addition, to support these tools, procedures, standards, formats were established, as well as the use of technology for warehouse management and purchases that would allow adequate inventory control. As the main effect of the proposal of the logistics system in the company is to increase the efficiency based on the costs related to the indicators of the average value of stock, turnover of stock and the average rate of coverage of the articles, which show a reduction in 19.75%, 19.75% and 2.01%, respectively. Finally, the feasibility of the project is evaluated for a later implementation, finding that it is economically feasible due to the net present value equal to S /. 1 109.20 and an internal rate of return of 20%, bringing with it a benefit-cost ratio with a value equal to 1.06.